Design of a solar and gas dryer to use coffee pulp in food processes in Peru - Camayo-Lapa Becquer Frauberth; Quispe-Solano Miguel Ángel; De La Cruz-Porta Erika Amelia; Asto-Hinojoza Roberto Cesar (Caspian Journal of Environmental Sciences)
In the central jungle region of Peru, within the wet processing of coffee, the coffee pulp is discarded. This objective is to design a dual solar and gas dryer with continuous operation, for the dehydration of waste from wet processing of coffee for human use. The proposed objective is part of a broader project to apply the circular economy in the use of waste from wet coffee processing financed by Pro Ciencia. The following procedure was followed. At first, a 100 kg/Bach capacity gas and solar system dryer was designed applying the proposed technology development methodology in mechanical engineering and secondly arriving at the construction of the prototype. The results are to have a design methodology and the built prototype of the dual dryer (solar and gas) of continuous and semi-automated operation that has a control panel to allow programming and monitoring the drying process in real time. At the end of the project, the proposal will allow a continuous dehydration of the coffee pulp with quality, low cost and the industrialization of its by-products such as coffee pulp flour, filters and functional drinks.